Ứng dụng diatomit làm chất phụ gia cho lớp phủ bảo vệ chống ăn mòn cho thép cacbon - Sơn, Nguyễn Anh; Dương, Nguyễn Thùy; Vũ, Phạm Gia; Trúc, Trịnh Anh (Vietnam Journal of Chemistry, 2014)
Diatomite is naturally occurring with over 63 % of silica in the chemical composition. This diatomite was introduced in waterborne epoxy for corrosion protection of carbon steel surface. The morphology of coatings was observed by Field Emission Scanning Electron Microscopy (FESEM). The Electrochemical Impedance Spectroscopy (EIS) method was used for characterized the corrosion protection of epoxy coating and epoxy coating containing diatomite. The results showed that incorporation of 15 % diatomite in waterborne epoxy coatings enhanced anticorrosion protection property of the coating. Keywords: Diatomite, waterborne epoxy coatings, anticorrosion protection